Input-output based system perturbation analysis of the environmental implications of rice hull utilization for power generation in the Philippines - Yu, Krista D. S. (Animo Repository, 2016)
Agriculture dependent economies commonly produce low-value products relative to industrialized economies. Converting agricultural waste into electricity will increase the value of engaging such activities. However, climate change also contributes immensely to the shifts in seasons thereby effecting agricultural yield and biomass production. This study analyzes the impact of using rice hull waste into electricity generation to economic activities and carbon emissions using an input-output (I-O) approach. The I-O model is widely used for illustrating the interdependent relationship between various economic sectors. This study extends the traditional I-O model such that it links the I-O table to another table composed of further subsectors not found in the original database, providing a more detailed snapshot of activities. The Philippine case is considered, given that rice is the main staple crop. However, the volume of rice production is insufficient which causes the Philippines to import rice from neighboring countries. Despite the high level of demand for rice in the Philippines, farmers tend to shift their production to higher valued crops. Alternatively, the by-product of rice production, rice hull, is an underutilized crop residue available in large quantities which may be used for power generation. The potential electricity contribution of rice hull can either reduce the power shortage that has been going on for the last decade or displace fossil fuel based electricity, at the same time, increase the value of rice production. Hence, government can reduce rice imports and service the utility demand of its constituents. © 2016, AIDIC Servizi S.r.l.